Distribution of Macrobiotus shonaicus Stec, Arakawa & Michalczyk, 2018 (Tardigrada: Eutardigrada: Macrobiotidae) in Japan - Sugiura, Kenta; Arakawa, Kazuharu; Matsumoto, Midori (Zootaxa, 2020)
To date, only seven species of Macrobiotidae (Parachela; Eutardigrada; Tardigrada) have been reported from Japan, including the recently described Macrobiotus shonaicus Stec et al., 2018 from the Shonai region of Japan. This species has flexible filaments on the egg processes and is known to proliferate only through sexual reproduction. Here, we report a multifaceted analysis of nine populations of M. shonaicus found on four Japanese islands. DNA sequencing of the cytochrome oxidase subunit I (COI) and internal transcribed spacer 2 (ITS-2) of the nine populations revealed 8 and 11 haplotypes, respectively. The extensive morphometric analysis showed considerably greater variability in the morphology of eggs than of animals. In addition to the morphological and molecular data, we confirmed the karyotype and found that all populations had a chromosome number of n = 6. Moreover, we observed and filmed mating behaviour between all studied populations of M. shonaicus. Our results clearly indicated that M. shonaicus is widely distributed throughout Japan.